Impact of Comorbidity of Bronchial Asthma and Type 2 Diabetes Mellitus on the Expression and Functional Activity of TLR2 and TLR4 Receptors - Yaroslav V. Radzyukevich; Ninel I. Kosyakova; Isabella R. Prokhorenko (Life, 2023)
Epidemiological data indicate the active progression of various forms of diabetes mellitus in patients with bronchial asthma (BA), but little is known about the mechanisms of comorbidity formation. TLR2 and TLR4 are involved in the progression of asthma and type 2 diabetes mellitus (T2DM). These receptors are involved in the inflammatory response to Gram(+) and Gram(−) bacteria, respectively, so changes in their expression may affect the predisposition of patients to bacteremia. The aim of this study was to analyze the expression and functional activity of toll-like receptor 2 and 4 (TLR2 and TLR4) on peripheral blood cells of patients with BA, T2DM, and BA + T2DM. The expression of TLR2 and TLR4 was analyzed by flow cytometry. Whole blood samples were incubated with lipopolysaccharides from E. coli (LPS) and lipoteichoic acid from S. pyogenes (LTA). The concentration of cytokines and soluble blood proteins was determined by ELISA. Patients with comorbid diseases showed a statistically significant increase in TLR2 expression on both monocytes and neutrophils compared with healthy donors and patients with BA. We found increased expression of TLR4 on the surface of blood monocytes from patients compared to donors. The activation of blood cells of patients and donors with LPS or LTA led to an increase in the expression of “fast” pro-inflammatory cytokines (TNF-α, IL-6). In patients with BA, the average production of TNF-α in response to endotoxin was two times higher than in other studied groups. The reactions of blood cells in patients with T2DM and BA + T2DM did not differ significantly. The expression and functional activity of TLR2 and TLR4 on the blood cells of patients with comorbid disease were similar to those only in patients with T2DM. The greatest increase in the synthesis of the pro-inflammatory cytokine TNF-α in response to LPS and LTA was observed in patients with BA, which can lead to an inadequate response to bacteremia.